Structure of engineering and clean and jerk in weightlifting high qualification of different sexes - V.G. Oleshko; V.V. Gamaliy; O.V. Antoniuk; A.V. Ivanov (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
Investigate the structure and propulsion technology breakthrough in weightlifting qualifications of different sexes with a weight bar in the area of 92-100% intensity. The study involved 220 men and 116 women. Video performed motor actions lifters, allowing the athlete to register force interactions with the keeper. Set the trend in the same type of force interaction with the bar for athletes of both sexes. Athletes apply maximum efforts in the final phases of acceleration and support the squat, the minimum - in the phase of depreciation. Established the distinctive features art by women lifting a barbell in the snatch and clean and jerk. The acceleration of the rod in the final phase of acceleration is considerably higher than that of men. It is proved that the structure of motor actions during the implementation of competitive exercises the same type of weightlifters of different sexes have distinctive features. This involves using a differentiated approach in the development of programs to improve technical skill separately for men and for women.